Cyclic AMP deficiency, modifier-mutations, and instability of the cr-1 phenotype - S. Said; H. F. Terenzi (Fungal Genetics Reports, 1979)
Cyclic AMP deficiency, modifier-mutations, and instability of the cr-1 phenotype